Gene-drives and active genetics: introduction to gene-drives and their implications for health and society - Bier, Ethan (Henry Stewart Talks, 2017)
Gene drives: overview, CRISPR/Cas9 technology, CRISPR/Cas9 DNA break repair, Gene-drive elements spread rapidly in a population, Active genetics: a new field, Gene-drive systems, Active genetics and drive effectors, DNA repair mechanisms, Mathematical modeling, Social and ethical considerations